A Simple Technique to Facilitate Treatment of Urethral Strictures with Optical Internal Urethrotomy - Konstantinos Stamatiou; Aggeliki Papadatou; Hippocrates Moschouris; Ioannis Kornezos; Anargiros Pavlis; Georgios Christopoulos (Case Reports in Urology)
Urethral stricture is a common condition that can lead to serious complications such as urinary infections and renal insufficiency secondary to urinary retention. Treatment options include catheterization, urethroplasty, endoscopic internal urethrotomy, and dilation. Optical internal urethrotomy offers faster recovery, minimal scarring, and less risk of infection, although recurrence is possible. However, technical difficulties associated with poor visualization of the stenosis or of the urethral lumen may increase procedural time and substantially increase the failure rates of internal urethrotomy. In this report we describe a technique for urethral catheterization via a suprapubic, percutaneous approach through the urinary bladder in order to facilitate endoscopic internal urethrotomy.